Fault-tolerant functional reactive programming (extended version). (7th May 2020) - PEREZ, IVAN; GOODLOE, ALWYN E.
Abstract: Highly critical application domains, like medicine and aerospace, require the use of strict design, implementation, and validation techniques. Functional languages have been used in these domains to develop synchronous dataflow programming languages for reactive systems. Causal stream functions and functional reactive programming (FRP) capture the essence of those languages in a way that is both elegant and robust. To guarantee that critical systems can operate under high stress over long periods of time, these applications require clear specifications of possible faults and hazards, and how they are being handled. Modeling failure is straightforward in functional languages, and many functional reactive abstractions incorporate support for failure or termination. However, handling unknown types of faults, and incorporating fault tolerance into FRP, requires a different construction and remains an open problem. This work demonstrates how to extend an existing functional reactive framework with fault tolerance features. At value level, we tag faulty signals with reliability and probability information and use random testing to inject faults and validate system properties encoded in temporal logic. At type level, we tag components with the kinds of faults they may exhibit and use type-level programming to obtain compile-time guarantees of key aspects of fault tolerance. Our approach is powerful enough to be used in systems with realistic complexity, and flexible enough to be used to guide system analysis and design, validate system properties in the presence of faults, perform runtime monitoring, and study the effects of different fault tolerance mechanisms.